Effects of Yucca schidigera extract on growth performance and antioxidative function of small intestine in broilers. Issue 3 (31st January 2019) - Sun, Dengsheng; Jin, Xiao; Camerlink, Irene; Tong, Manman; Su, Junling; Zhao, Fei; Yan, Sumei; Shi, Binlin
Abstract: Dietary Yucca schidigera extract (YSE) could enhance immune function in broilers, which was attributed primarily to its saponin components. However, YSE also contains phenolic compounds which possess antioxidant ability. This study tested the effects of YSE on growth performance of broilers, its antioxidative enzyme activities and corresponding gene expressions in the small intestine. A total of 128 15‐day‐old broilers were randomly assigned to 4 treatments: corn‐soya bean meal as the basal control diet or the basal diet containing either 100, 200 or 300 mg/kg of YSE. Each treatment consisted of four replicate pens with eight broilers per pen. The experiment lasted 28 days which was divided into a grower period (day: 15–28) and a finisher period (day: 29–42). On day 28 and day 42 body weight (BW), feed intake (FI) and feed conversion rate (FCR) were recorded. Duodenum, jejunum and ileum were collected to analyse superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) activities, malondialdehyde (MDA) concentrations, total antioxidant capacity (T‐AOC) and gene expressions of SOD, CAT, GPx. The results showed that during the grower period a diet including 100 mg/kg YSE improved CAT capacity in the ileum, tended to increase activities of GPx in the duodenum, and further showed enhancing tendencies in SOD and GPx abilities in ileum. Gene expressions of CAT, SOD and GPx in the ileum tended to upregulate at 100 mg/kg YSE level. In the finisher period and over the whole period, all YSE groups had a reduced FI compared to the control group without compromising BW; 100 and 200 mg/kg YSE significantly improved FCR. In conclusion, the improved growth performance of broilers during the finisher period may be due to enhanced antioxidative ability in the grower period with YSE supplementation. This study provided evidence of using YSE as an additive to enhance growth in broilers.